A large-scale water-harvesting device with β-Al(OH)3 microcone arrays by simple hydrothermal synthesis. Issue 48 (28th November 2017) - Cho, Handong; Park, Byungrak; Kim, Moonsu; Lee, Sangmin; Hwang, Woonbong
Abstract : Here we report a novel approach to fabricate conical microstructures on aluminum substrates using a cost-effective and scalable hydrothermal synthesis method. Abstract : As the scarcity of fresh water emerges as a major global problem, fog-water harvesting is considered as a sustainable method for obtaining water resources. Although water-harvesting technologies based on special wetting surfaces have attracted considerable interest because of their high efficiency, many problems remain, including high cost and difficulties in the fabrication of special wetting surfaces. Here we report a novel approach to fabricate conical microstructures on aluminum substrates using a cost-effective and scalable hydrothermal synthesis method. Due to their morphological features, the microcone surfaces exhibit extremely high wettability and excellent water-collection capacity. Furthermore, we suggest a practical water-harvesting device that allows an effective and sustainable way to collect fresh water from moist air and has enhanced adaptability to environmental conditions. These features enable us to develop a highly promising water-harvesting system for overcoming problems associated with water shortage.